STRATEGIES TO IMPROVE LOCAL GOVERNMENT FINANCIAL PERFORMANCE - Fanika; Khairudin; Aminah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This research aims to analyze the effect of PAD, capital expenditure, and balancing funds on the financial performance of local governments. With all regencies/cities in Lampung Province as the population in this study and 15 regencies/cities as samples. The data used in this study is in the form of secondary data and the data processing method used is multiple linear regression. The results of this study are: (1) PAD has a significant positive effect on the Financial Performance of Local Governments. (2) Capital Expenditure has a significant negative effect on the Financial Performance of Local Governments. (3) The Balancing Fund has a significant negative effect on the Financial Performance of Local Governments.